2021
DOI: 10.1038/s41598-021-89289-y
|View full text |Cite
|
Sign up to set email alerts
|

Response to novelty induced by change in size and complexity of familiar objects in Lister-Hooded rats, a follow-up of 2019 study

Abstract: This study examines the relationship between the change in size and change in complexity of well-known/familiarized objects and exploratory activity regulation in rats. In our experiment, the rats were exposed to three types of environmental novelty in a well-familiarized chamber: (1) addition of new tunnels to the chamber, (2) increased size of a familiarized tunnel, and (3) increased complexity of the existing tunnels. The animals responded to the addition of new tunnels with a significant behavioural shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…The results obtained for the Add and MovAdd groups seem to corroborate this assumption. The results of our previous studies [27,28] are also confirmed,…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The results obtained for the Add and MovAdd groups seem to corroborate this assumption. The results of our previous studies [27,28] are also confirmed,…”
Section: Discussionsupporting
confidence: 79%
“…The results obtained for the Add and MovAdd groups seem to corroborate this assumption. The results of our previous studies [ 27 , 28 ] are also confirmed, which showed that an increase in the complexity of the environment through the addition of tunnels triggers a more intensive exploratory activity in rats.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations